503 Cardio-Vascular Burden of Narcolepsy Disease (CV-BOND): a Real-World Evidence Study. (3rd May 2021) - Ben-Joseph, Rami; Saad, Ragy; Dabrowski, Elizabeth; Taylor, Ben; Gallucci, Sophia; Somers, Virend
Abstract: Introduction: Narcolepsy is a rare, lifelong disorder that requires long-term treatment and is associated with multiple comorbidities, including cardiovascular conditions. Many available treatments have cardiovascular-related warnings and precautions in their labels. The objective of this study was to estimate the incidence of cardiovascular comorbidities in adult patients with a narcolepsy diagnosis in the US. Methods: Claims from IBM® MarketScan®, an administrative claims database, between January 2014 and June 2019 were analyzed. Eligible patients were ≥18 years and had continuous medical and prescription coverage (gaps <30 days allowed). The narcolepsy cohort was defined by ≥2 outpatient claims containing a diagnosis of narcolepsy type 1 or type 2 on separate days and no more than 6 months apart, with ≥1 non-diagnostic office-visit. Non-narcolepsy patients were matched 3:1 to narcolepsy patients by calendar date of cohort entry, age, gender, US geographic region, and insurance type. Each incidence calculation required a 6 month wash-out period prior to cohort entry. Differences between cohorts were evaluated using a Cox proportional hazard model adjusted for age, gender, region, insurance type, and relevant morbidities/comorbidities and medications in the baseline period. Results: Of 54, 239, 110 adults in the database, 12, 816 and 38, 441 were included in the narcolepsy and matched non-narcolepsy cohort. Approximately 67% were female patients and mean age was approximately 38 years in both cohorts. Incidence rates (per 1, 000 person-years) for newly recorded cardiovascular comorbidities or events in narcolepsy/non-narcolepsy were: CVD without hypertension (13.29/7.99), MACE+ (11.75/6.86), heart failure (5.72/3.41), stroke (4.28/2.17), ischemic stroke (3.69/1.91), edema (9.84/4.22), and a composite of stroke, atrial fibrillation, and edema (17.73/8.88). Conclusion: Physicians should consider the increased cardiovascular risk when considering risk modification strategies and treatment options for narcolepsy patients. Further research is needed to understand treatment-specific risks. Support (if any): Jazz Pharmaceuticals